Body fat distribution and components of leisure-time physical activity in post-menopausal women: Cross-sectional study among users of Brazilian Public Healthcare System - Locci, Bruna [UNESP]; Turi, Bruna C. [UNESP]; Araújo, Lia G. M. [UNESP]; Fernandes, Rômulo A. [UNESP]; Codogno, Jamile S. [UNESP]; Monteiro, Henrique L. [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2015)
Study design: Cross-sectional study. Aim: To investigate whether leisure-time physical activity can impact on fat mass distribution in post-menopausal women, users of Brazilian Public Healthcare System. Methods: The sample was composed by 176 postmenopausal women aged e 50 years. Body composition was expressed as quantity in grams of total and central fat mass and lean mass, obtained by dual Xray absorptiometry (DXA). To assess leisure-time physical activity we used the second section of Baecke's questionnaire considering intensity, duration and prior engagement in physical activity practice. Economic status was assessed by a specific and previously validated Brazilian questionnaire. Spearman correlation and linear regression assessed the relationship between indicators of body fat and components of lei-sure-time physical activity. Results: Most part of participants was middle-income, with mean age of 65,9 ± 8 years and the onset of menopause occurred at 47,5 ± 6 years. We observed relationship between higher intensity and prior engagement in leisure-time physical activities with lower levels of central fat, however, when adjusted for some confounding factors, such as this relationship is no longer statistical significant. Conclusion: For this population, intensity, duration and prior engagement in leisure-time physical activity are insufficient to cause significant changes in body composition.
Distribuição da gordura corporal e componentes da prática de atividades físicas no lazer em mulheres pósclimatério: Estudo transversal com usuárias do Sistema Único de Saúde
Keywords: Menopause.; Motor activity; Obesity